Status Kepemilikan Tanah Hasil Konversi Hak Barat Berdasarkan UU NO. 5 Tahun 1960 Tentang Peraturan Dasar Pokok-Pokok Agraria Dihubungkan Dengan PP NO. 24 Tahun 1997 Tentang Pendaftaran Tanah - Ulfia Hasanah (Fakultas Hukum Universitas Riau, 2012)
With the enactment of Law No. 5 of 1960 concerning the Basic Agrarian fundamental changes to the agrarian law in Indonesia, especially in the area of ​​land. As for the legal basis for the conversion of land rights is the second part of the Act concerning the provisions of the conversion consists of nine chapters that govern the conversion of three types, namely: the conversion of land resulting from Indonesia's rights, conversion rights to land former Autonomous and conversion of land rights from the rights of the west.